Comparative analysis of nutritional composition and droplet size of coconut milk due to dilution and emulsification - Abdullah, Z.; Taip, F. S.; Mustapa Kamal, S. M. (Rynnye Lyan Resources, 2022)
The high-fat content of coconut milk leads to instability of the emulsion and becomes the major limitation for its application in the food and beverage industries. It is also high in calories, which becomes a major debate among the consumers. Dilution and emulsification are important processes that are used to reduce the effect of high fat during the preservation process. In this study, water, sodium caseinate, and maltodextrin were added to the coconut milk. A sonicator and a high-shear homogenizer were used to homogenize the droplet. This study aimed to evaluate the effect of dilution and emulsification on the nutritional quality and stability of the emulsion. The nutritional composition was determined using proximate analysis. The stability of the emulsion was determined based on the properties of the droplets via particle size and microscopic analyses. The dilution process reduced the fat content; however, the addition of additives altered the nutritional quality of the emulsion, especially protein and carbohydrate content. It was also found that the emulsification process improves the particle size of the droplet as it creates a uniform size of the droplet and reduces the primary particle size to less than 6 μm. However, only the sonicated coconut milk has high stability with a creaming index of 0%.